2018
DOI: 10.1111/dth.12715
|View full text |Cite
|
Sign up to set email alerts
|

The effect of continuous high versus low dose oral isotretinoin regimens on dermcidin expression in patients with moderate to severe acne vulgaris

Abstract: The continuous low dose (LD) isotretinoin is frequently used in the treatment regimen for acne vulgaris. However, data about its antimicrobial are lacking. The present study aimed to investigate dermcidin expression and the effects of low and conventional dose isotretinoin on its expression in acne vulgaris patients. Skin dermcidin expression was investigated in 30 patients with moderate–severe acne vulgaris and 15 healthy control subjects using ELISA. 15 patients were given continuous low‐dose isotretinoin (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Nakano et al () investigated the sweat concentration of DCD in patients with acne vulgaris and found lower DCD levels in acne patients than in healthy controls. El Aziz Ragab, Omar, Collier, El‐Wafa, and Gomaa () performed skin biopsies to detect DCD expression using ELISA in acne patients and healthy controls and reported decreased DCD levels in acne patients. In our study, we also found decreased plasma levels of DCD in acne patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakano et al () investigated the sweat concentration of DCD in patients with acne vulgaris and found lower DCD levels in acne patients than in healthy controls. El Aziz Ragab, Omar, Collier, El‐Wafa, and Gomaa () performed skin biopsies to detect DCD expression using ELISA in acne patients and healthy controls and reported decreased DCD levels in acne patients. In our study, we also found decreased plasma levels of DCD in acne patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by El Aziz Ragab et al, the effect of continuous low‐dose and conventional high‐dose isotretinoin treatment on DCD levels was examined in acne patients. It was noted that both regimens resulted in increased DCD levels (El Aziz Ragab et al, ). We also found that DCD levels were significantly increased after isotretinoin therapy in our patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Dermcidin level was significantly low in the studied cohort of acne vulgaris patients and both isotretinoin regimens significantly raised dermcidin levels compared to pretreatment values. No significant difference in relapse rate over a 12‐month follow‐up period was noted among the two isotretinoin regimens (El Aziz Ragab, Omar, Collier, El‐Wafa, & Gomaa, ).…”
Section: Indications Of Low‐dose Isotretinoin In Dermatologymentioning
confidence: 92%
“…El Aziz Ragab et al noted that dermcidin was significantly lower in acne vulgaris patients. They noted that both ISO regimens (low‐dose ISO [20 mg/kg/day] and the conventional high dose [0.5 mg/kg/day]), significantly raised dermcidin levels compared to pretreatment values with no significant relapse after 12 months of follow‐up (El Aziz Ragab, Omar, Collier, El‐Wafa, & Gomaa, ). Lowering the treating dose of ISO may lessen the related neuropsychiatric adverse effects with optimum therapeutic efficacy compared to the standard dose.…”
Section: Low‐dose Iso As a “New Era” In Acne Managementmentioning
confidence: 99%